Eksplorasi Potensi Airtanah pada Kawasan Industri Air Mineral Dalam Kemasan, Cemplang, Bogor - Roh Santoso Budi Waspodo (Jurnal Keteknikan Pertanian, 2015)
Exploration of water resources is an attempt to provide water accesibility for society’s. Required in-depth study of geological analysis-hydrogeological springs and groundwater that it will be processed into clean water to support communities. The intent of this study was to determine the geoelectric-hydrogeological conditions through the distribution characteristic of the aquifer by resistivity rocks around Cemplang, Bogor. The purpose of this investigation was to provide a data where groundwater sources are used for industrial mineral water The exploration results obtained by the location of shallow groundwater in the range between 2-14 m below the surface of the local soil. Free groundwater depth (shallow groundwater) conducted in the study area, groundwater depths ranging between 2-8 m below ground surface (bmt) local. The groundwater is estimated from Mount Salak as a groundwater resource, The estimation geoelectric investigation area is resistivity 3-400 Ωm. Rock aquifer consists of sandy loam, silty sand and sand hydraulic conductivity estimated 3-40 m/day. Layer has a smaller resistivity of 13 Ωm and is at a depth of 17 m bmt. The slopes of this research area is 0017 to obtain the potential of groundwater in at 18,947.37 m3/day, equivalent as 219.30 liters/sec.